Do Immigrants Improve Their Housing Quality When They Move? Evidence from the German Socio-Economic Panel - William A. V. Clark; Anita I. Drever (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
Previous research using the German Socio-Economic Panel showed that immigrants moved slightly more fre-quently than native-born Germans. The research in this paper extends that work and examines the extent to which this increased mobility is translated into improved housing quality. Overall, we find that all sample households have improved their housing status over time, and that both the immigrant and native-born German households gain additional housing space when they move. At the same time, immigrant households have yet to achieve parity in the number of rooms, square meters, or levels of satisfaction. Interestingly, even though both immigrants and native-born Germans have increased the amount of space they consume, they are both less satisfied than a decade ago. The logit models emphasize that the classic dimensions - age, tenure choice and household size - explain the likelihood of increasing space with mobility. The models are much less accurate predictors of levels of satisfaction or degree of building renovation.
Keywords: 330; Wohnung; Wohnungswechsel; Besitzformwahl; Vergleich; Deutschland; Migranten